Efficacy of Three Varietal Toxins of Bacillus thuringiensis Tested against some Important forest Insect Pests of Multipurpose forest Tree Species - Kalla, Shamila; Lall, R. B. (Indian Forester, 2000)
Effectiveness of three varietal toxins of Bacillus thuringiensis viz. var. thuringiensis (BTB) and two products of var. kurstaki i.e. (LDC) and (Dipel) @ 2.0, 1.5, 1.0, 0.5, 0.25 and 0.10% were tested against ten important pests offorest trees in nurseries and plantations at Tropical Forest Research Institute, Jabalpur (M.P.). The results indicate that all the defoliators are highly susceptible to the microbial pesticide B. thuringiensis and spraying the pesticide at 1.5% concentration was found to be most effective in controlling the pests irrespective of the toxins.